2020
DOI: 10.1103/physrevx.10.011012
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Surface and Bulk Ferromagnetism Mimics Skyrmion Hall Effect in a Topological Insulator

Abstract: Here we report the investigation of the anomalous Hall effect in the magnetically doped topological insulator (V,Bi,Sb)2Te3. We find it contains two contributions of opposite sign. Both components are found to depend differently on carrier density, leading to a sign inversion of the total anomalous Hall effect as a function of applied gate voltage. The two contributions are found to have different magnetization reversal fields, which in combination with a temperature dependent study points towards the coexiste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 31 publications
(46 reference statements)
6
39
0
Order By: Relevance
“…5 a, b, confirming that the TH effect-like hump feature observed in our Cr-doped TI/TI/V-doped TI sandwiches is indeed from the superposition of two AH effects with opposite signs. Our findings here, together with two prior studies 40 , 41 , suggest humps/dips features along with the AH effect observed in a number of bilayer heterostructure samples might not be induced by the formation of the chiral spin textures in samples 31 , 42 45 . The TH-like hump feature observed in these bilayer heterostructures is likely also due to the coexistence of two decoupled FM orders.…”
Section: Resultssupporting
confidence: 78%
“…5 a, b, confirming that the TH effect-like hump feature observed in our Cr-doped TI/TI/V-doped TI sandwiches is indeed from the superposition of two AH effects with opposite signs. Our findings here, together with two prior studies 40 , 41 , suggest humps/dips features along with the AH effect observed in a number of bilayer heterostructure samples might not be induced by the formation of the chiral spin textures in samples 31 , 42 45 . The TH-like hump feature observed in these bilayer heterostructures is likely also due to the coexistence of two decoupled FM orders.…”
Section: Resultssupporting
confidence: 78%
“…For example, as shown in Figure 3, this feature may also arise in the Hall data as a consequence of two coexisting anomalous Hall signatures with opposite polarity, even when no skyrmions are present in the system. [ 231–233 ] Thus, multiple observations are necessary to conclude the presence of THE. In Figure 11, the “hump‐like” feature is strongly associated with the observation of a finite ρ xx , and disappears entirely in the QAHE regime when ρ yx is quantized and ρ xx = 0.…”
Section: Recent Results In Topological Insulator (Ti) – Magnetic Materials (Mm) Heterostructuresmentioning
confidence: 99%
“…The quantum anomalous Hall effect (QAHE), first discovered in Cr/V-doped (Bi,Sb) 2 Te 3 1 3 , has opened new avenues for academic studies into solid state manifestations of axion electrodynamics 4 9 and unconventional magnetism 10 14 . However, the metrological precision of Hall resistance quantization at zero magnetic field so far remains limited to temperature of the order of 20 mK 15 17 , while the Curie temperature ( T C ) in the involved materials is as high as 20 K 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…As the Hall resistance takes on values clearly below h / e 2 (where h is Planck’s constant and e the elementary charge) at temperatures above 1 K or so, well below T C , where the bulk remains robustly ferromagnetic, the nonquantized Hall resistance can in principle originate from the ordinary bulk states in the absence of any chiral edge channel. Moreover, the possible presence of two distinct ferromagnetic phases 14 and the otherwise rich magnetic behavior reported at low temperature 10 , 13 , 18 21 leave open the possibility of a second phase transition being involved, and thus possibly playing a role in the edge channel formation at some temperature below T C .…”
Section: Introductionmentioning
confidence: 99%